MaBareBare, a rumour of a dream - Mahashe, Tebogo George (Michaelis School of Fine Art, 2019)
This multi-part PhD submission builds on Premesh Lalu’s (2009) assertion that an understanding of the subjectivity of the colonised is irrecoverable from the colonial archive. It does this through my quest for, and my encounter with, fragments associated with an episode of travel to Berlin by some Balobedu in 1897 and, subsequently, by myself in the present. This confrontation with the archive facilitates a meditation on an idea of khelobedu, as a subject effectively trapped by classical anthropology struggling to understand it (khelobedu) as a contemporary reality. Khelobedu is, amongst other things, the language and religion of Balobedu from north-eastern Limpopo province in South Africa. It is used in this PhD project as a conceptual tool to express the complexity inherent in the multiple subjectivities that I inhabit, encounter, respond to and mobilise; that, effectively, I practice. I adopt a range of creative fine art methods to engage khelobedu outside of the prescribed and constraining methodologies of established academic disciplines historically developed as appropriate for the study of African cultural life. My methods involve travelling, dreaming and creative practice as process. Travel has entailed my journeys to Berlin to consult colonial archives related to Balobedu, as well as wider travel to other places (such as Dakar) to visit contemporary art institutions and attend key events profiling my chosen artistic methodologies. I have employed Balobedu dream practices as a way of understanding, and claiming, Balobedu subjectivity, as premised on political agency and opacity. The methodology of creative practice has necessitated the making and staging of art exhibitions and installations within the contemporary art circuit; and persistent documentation of my installations and travels (conversations, cafe encounters and so forth) as artistic process as well as of the demands of practice as a subject itself — specifically instituting several iterations of a camera obscura installation as a response to my dissatisfaction with the documentary impulse that I understand to 'trap’ khelobedu. These methodologies emphasise the idea of play and participation aimed at forming a habit of practice. They collectively contribute to the PhD project as both diagnostic of, and a way of challenging and offering a resolution to, the problem of coloniality in the academy. These processes of practice reiterate that the subjectivity of Balobedu is not just to be sought in the colonial archive but persists, and is recoverable, in contemporary Balobedu such as myself. Through the practices at the heart of this PhD project, I establish that my being a Molobedu cannot be separated from my positions as artist and academic, and so insist on an understanding of Balobedu as contemporaneous, always 'in time’ with all of time’s complexities, recognisable to contemporary subjectivities. The imperative to resist coloniality and to risk a departure from the conventions of the PhD in order to imagine and express khelobedu determines the form of the thesis as an open-ended proposition, emphasising practice and, for now, provisionality.